(untitled) (Elmergib Journal of Human Sciences, 2026)
Trade was the lifeblood of societies in the ancient world, including Al-Hirah, which functioned as a major commercial center and a vital link between regions of goods and commodities in the East and the West. The inhabitants of Al-Hirah accumulated great wealth from trade, which resulted in significant economic, scientific, and cultural impacts on them and on other peoples during the pre-Islamic period. This study aims to clarify the importance of Al-Hirah’s commercial location, as well as the role of its inhabitants in building human civilization. The study reached several conclusions, including the keen interest of the kings and merchants of Al-Hirah in trade, taking advantage of its geographical position. Moreover, Al-Hirah became a meeting point for ancient cultures that blended with the local culture, leading to economic, scientific, and cultural development in the region.